Climate change disclosure, institutional ownership, and firm performance: Evidence from mining industry in Indonesia and Malaysia - Aulia, Desta Rahma; Utami, Evy Rahman; Kresnawati, Etik (Journal of Accounting and Investment, 2026)
Research aims: This study investigates the effect of climate change disclosure on firm performance and the moderating role of institutional ownership in this relationship in an emerging market. Design/Methodology/Approach: This study employs a quantitative method using secondary data from mining companies in Indonesia and Malaysia for the 2022-2024 period. The sample was selected through a purposive sampling method, and panel-data regression with random effect model (REM) was analyzed using EViews 12.Research findings: The results show that climate change disclosure has a positive effect on firm performance. However, in emerging countries where institutional investors may act passively and show little concern in sustainability issues, this study emphasizes the limited role of institutional ownership on business environmental standards.Theoretical contribution/Originality: This study contributes to the literature on the role of institutional ownership as a corporate governance mechanism in driving improved corporate performance through climate disclosure in mining companies in Indonesia and Malaysia.Practitioner/Policy implication: The findings suggest that firms need to enhance the transparency of their climate change disclosure, as it may contribute positively to firm performance and strengthen investor trust. In addition, regulators are encouraged to promote more comprehensive climate-related disclosure practices in order to support sustainable business development. Research limitation/Implication: This study is limited to mining companies in Indonesia and Malaysia over the 2022–2024 observation period. Future research is recommended to extend the analysis to other industries and countries, as well as to use a longer observation period in order to obtain more robust and comprehensive findings.